An Empirical Study on Residents' Consumption Changes Based on the Development of Commercial Annuity - Zhou, Jiaxuan (Archives of Business Research, 2020)
The relationship between the level of pension insurance development and the consumption of Chinese residents is a topic of constant debate. However, few scholars have analyzed residents' consumption behavior based on the level of commercial annuity development. Using China's 2010-2018 inter-provincial panel data, this article builds a dynamic panel regression model to explore the impact of the development of commercial annuities on household consumption and its structure. In addition, the paper also compares the impact of the protection levels of basic pension insurance and commercial annuity on household consumption. The results show that the per capita disposable income of residents is still the main factor that promotes residents’ consumption. The improvement of commercial annuity and basic endowment insurance will help to promote residents' consumption, and the effect of commercial annuity's promotion on residents' consumption is more significant. In promoting the optimization and upgrading of consumption structure, commercial annuity insurance plays a more significant role than residents' income level and basic pension insurance. Based on the regression results, this article suggests that efforts should be made to increase the income level of residents and promote consumption from the root cause. At the same time, it is necessary to improve the commercial pension insurance system as soon as possible and steadily promote the coordinated development of the "three pillars" pension insurance system.